On Context Theory and Interactive Language Teaching - Liu, Jixin (International Journal for Innovation Education and Research, 2015)
In this paper, the author explores the importance of context in interactive language teaching and how to make the classroom activities interactive through the application of context theory from the perspective of comprehension (listening, reading) and production (speaking and writing) and how to build context in foreign language classroom in accordance with the linguistic rules of English to promote the students’ communicative competence in the context.